Social Entrepreneurship in the Irish State-funded Third Sector - Byrne, Danielle Léa (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2022)
The study seeks to determine the extent and nature of social entrepreneurship in a population of Irish third sector organisations (TSOs) in receipt of state funding, and to explain why some TSOs may be more socially entrepreneurial than others. The study extends existing literature in identifying not only social entrepreneurial behaviours but in exploring their manifestation and causation. The study is located in a jurisdiction where the state is central to funding the third sector. By applying a scale of social entrepreneurial orientation (SEO) in a survey of a random sample of TSOs and subsequent quota-based interviews, the study finds a substantial cohort of TSOs with high levels of SEO, regardless of levels of state funding or earned income. A focus on the needs of a defined community is found to enable diversification and innovation. Resource mobilisation here manifests in bricolage of both financial and nonfinancial resources. Opportunity pursuit often involves collaborative relationships with the state. TSOs with a strong professional or occupational culture are found to have variable or lower levels of SEO, to be tied to a specific activity, and to be reluctant to diversify - but may pursue expansion of - existing services. The study makes a distinctive contribution in the robustness of its population and sampling; in the integration of quantitative and qualitative methods to achieve both breadth and depth of investigation; in developing, using and validating SEO as a measure of social entrepreneurship; in developing an evidence based understanding of the characteristics of social entrepreneurship; in confounding assumptions of the centrality of earned income strategies in this field; and in going some way to explain the differences in social entrepreneurialism among TSOs.
APPROVED
Keywords: Ireland; Nonprofit; Third Sector; Entrepreneurial orientation; Social entrepreneurship; Government funding